(untitled) (Reflection and Critique Law Magazine, 2022)
In 2020, the world was surprised by a deadly and completely unknown virus, a situation that led to a catastrophic pandemic. Therefore, this article discusses the negative reflexes caused by the event, keeping in focus a theme already widely known: domestic violence. In addition, we will discuss the feasibility of the measures that have been adopted to combat the increase in this index, specifically with regard to the use of technology. To this end, we will expose several of the measures adopted and their strengths and weaknesses, in order, through equalization, to reach the conclusion of which of these would be the best measure to be taken. Finally, we will raise pertinent questions about the theme and its real effectiveness in the day-to-day lives of women who suffer domestic violence.